1992
DOI: 10.1073/pnas.89.4.1256
|View full text |Cite
|
Sign up to set email alerts
|

Cardiostimulatory and antiarrhythmic activity of tubulin-binding agents.

Abstract: Rhythmic, spontaneously pulsating cardiac cells cultured from newborn rats are imediately stmulated to beat faster by addition of a number of tubulin-binding agents but not by their non-tubulin-binding an .The tubulinbinding agents tested incde vinbastine, crie, navelbine, two analogs of vinblastine (S12362 and S12363), nocodazode, colchicne, and podophylotoxin. In addi to binding tubulin, all ofthe above agents also depolymerize microtubules. Tubulin-binding agents such as colchicine, the vinca alkaloids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
4
28
1
Order By: Relevance
“…Returning to the cardiac effect of microtubule disruption, it has been shown that colchicine treatment accelerates the beating frequency in neonatal cardiac cells. 14,15 This effect could also be explained by the increase in I Ca that we report. However, after shorter periods of colchicine treatment than ours, some authors did not find an effect on contraction in either control or hypertrophied myocytes.…”
Section: Discussionmentioning
confidence: 63%
“…Returning to the cardiac effect of microtubule disruption, it has been shown that colchicine treatment accelerates the beating frequency in neonatal cardiac cells. 14,15 This effect could also be explained by the increase in I Ca that we report. However, after shorter periods of colchicine treatment than ours, some authors did not find an effect on contraction in either control or hypertrophied myocytes.…”
Section: Discussionmentioning
confidence: 63%
“…Microtubule disruption increases contractility in various cell types (Danowski, 1989;Lampidis et al, 1992;Kolodney and Elson, 1995;Sheridan et al, 1996;Canman and Bement, 1997). This process is accompanied by an increase of MLC phosphorylation (Kolodney and Elson, 1995) that can be a consequence of augmentation of Rho activity (Ren et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Microtubule disruption can inhibit the protective effects of ischemic preconditioning and isoflurane-induced myocardial preconditioning [9, 10]. In cardiac cells from newborn rats, disruption of microtubules has been found to stimulate the rate of spontaneous contraction [11]. Tubulin-binding agents that effectively stabilize microtubules have been reported to reverse adriamycin-induced arrhythmias and to affect the probability of eliciting stretch-induced arrhythmia in rabbits [11, 12].…”
Section: Introductionmentioning
confidence: 99%